Mapping the Evaluation of Problem-Oriented Pedagogies in Higher Education: A Systematic Literature Review - Renae Acton (MDPI AG, 2019)
Problem-oriented pedagogies have emerged as strategic way for universities to respond to an international higher education agenda that increasingly prioritises innovative, student-centred learning, and the cultivation of both civic and employability competences. Alongside this pedagogic shift is a policy-driven emphasis on monitoring teaching and learning for quality assurance purposes. This article aims to untangle the ways problem- and inquiry-based pedagogies are currently evaluated in universities, and thus consider how 'quality' implementation, and the effects of this suite of pedagogic approaches, might be better understood, practised, and measured. Taking a systematic approach to the review of the literature, the article maps evaluation methods that assess the effectiveness of problem-oriented and inquiry-based pedagogies implemented in university settings. The key findings include that evaluation methods in the field (i) prioritise qualification-related outcomes, (ii) are limited in scale and scope, and (iii) often function as demonstrations of performativity rather than as part of an ongoing improvement cycle. The article argues that evaluations that take a multi-method approach from the perspective of a range of stakeholders, with an exploration of civic and social competences in addition to employability outcomes, would significantly strengthen the field.